Method for preparing lithium iron phosphate from ferric hydroxyphosphate, and use thereof

JP2025009708AActive Publication Date: 2025-01-20HUBEI RT ADVANCED MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023198880
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-05
Filing Date
2023-11-24
Publication Date
2025-01-20
Estimated Expiration
2043-11-24

AI Technical Summary

Benefits of technology

【0028】 本発明の実施例に係るヒドロキシリン酸鉄からリン酸鉄リチウムを製造する方法は、チタンホワイトの副生成物である硫酸第一鉄を利用して硫酸鉄を生成し、他の材料を加えて反応させた後、異なる鉄リン比を有するヒドロキシリン酸鉄を生成し、次に異なる焼結プロセスを経て、鉄リン比が高く比表面積が高いヒドロキシリン酸鉄の製品と、鉄リン比が低く比表面積が低いヒドロキシリン酸鉄の製品とを得る。鉄リン比が高く比表面積が高いヒドロキシリン酸鉄と、鉄リン比が低く比表面積が低いヒドロキシリン酸鉄とを混合してから、リチウム源及び鉄源と所定の割合で混合した後、炭素源及び添加剤を加えて混合材料を形成し、混合材料をサンドミリング、噴霧乾燥、焼結、篩分け、バッチ合成、包装などの工程を経てリン酸鉄リチウムの製品を得ることができる。本方法は、鉄リン比が高いヒドロキシリン酸鉄と、鉄リン比が低いヒドロキシリン酸鉄とを混合して組み合わせ、2種類のヒドロキシリン酸鉄を混合して組み合わせることにより、大粒子と小粒子との組み合わせを形成し、リン酸鉄リチウム材料のプレス密度を向上させるとともに、電気化学的性能を向上させるのに役立つ。また、本方法に必要な反応温度が低く、反応時間が短く、設備に対する要求が低く、プロセスフローが簡単であり、製造効率を向上させ、大規模な工業的製造への適用に適する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009708000001_ABST
    Figure 2025009708000001_ABST
Patent Text Reader

Abstract

To provide a method for preparing lithium iron phosphate that has high production efficiency and low production cost, and is suitable for application in large-scale industrial production.SOLUTION: A method for preparing lithium iron phosphate comprises: adding hydrogen peroxide, phosphoric acid, an ammonium dihydrogen phosphate solution and ammonia water to a purified ferrous sulfate solution to form a mixed slurry, maintaining the temperature of the mixed slurry for a period of time, and then subjecting the same to washing with water and filter pressing so as to form iron hydroxyl phosphate precursors having different iron-phosphorus ratios; performing flash drying and high-temperature sintering to obtain iron hydroxyl phosphate precursors having different iron-phosphorus ratios and different specific surface areas, and crushing and mixing the same to obtain finished iron hydroxyl phosphate products; and mixing iron hydroxyl phosphate having a high iron-phosphorus ratio with iron hydroxyl phosphate having a low iron-phosphorus ratio at a certain ratio, proportioning the resulting mixture, a lithium source and an iron source at a certain ratio, and adding a carbon source and an additive thereto to form a mixture, and subjecting the mixture to steps of ball milling, sand milling, spray drying, sintering, crushing, screening, batch synthesis, packaging, etc., so as to obtain a finished lithium iron phosphate product.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of a method for producing a lithium-ion battery positive electrode material, in particular to a method and application for producing lithium iron phosphate from iron hydroxyphosphate. [Background technology]

[0002] Lithium iron phosphate cathode material is the most rapidly developing lithium battery cathode material in China. Its raw material sources are wide and inexpensive, and it has been widely applied in the domestic battery industry in China in fields such as automobiles, power tools, energy storage devices, emergency power supplies, and mobile power supplies. New energy electric vehicles are the main application field, and lithium iron phosphate accounts for about 45% or more of the cathode material of lithium batteries. Compared with other cathode materials, lithium iron phosphate has the advantages of safety, environmental friendliness, low cost, long cycle life, good high temperature performance, etc., and is one of the most promising lithium ion battery cathode materials. At present, the methods for producing lithium iron phosphate mainly include solid-phase method, carbothermal reduction method, sol-gel template method, etc.

[0003] For example, CN105024073A discloses iron hydroxyphosphate, a material for the positive electrode of a lithium ion battery, and a method for preparing the same. The molecular formula of the material for the positive electrode of a lithium ion battery is Fe 2.95 (PO4) 2 (OH) 2 The manufacturing method is H 3 PO 4 solution, FeCl 3 The solid powder is mixed with water to be uniform, and then methyltriethylammonium chloride is added to adjust the pH to 2.0-3.5. The temperature is controlled at 150-200°C to carry out hydrothermal synthesis reaction for 30 hours to obtain a reaction liquid. The reaction liquid is centrifuged, washed, and dried to obtain Fe. 2.95 (PO4) 2 (OH) 2 The aim is to obtain

[0004] In the journal "Research on the performance of lithium iron phosphate produced from hydroxyiron phosphate as a positive electrode material for lithium-ion batteries," the researchers synthesized hydroxyiron phosphate using waste iron phosphate, a by-product of the phosphorus chemical industry, phosphoric acid, and hydrogen peroxide as raw materials to produce lithium iron phosphate.

[0005] However, the above method requires high reaction temperature, long reaction time, strict reaction conditions, high requirements for production equipment, and low production efficiency, which does not meet the current market need to reduce the cost of lithium iron phosphate. In addition, the above method requires high raw material costs, and the impurities in the final product are difficult to remove, which affects the product performance of the subsequent iron hydroxyphosphate and the product performance of lithium iron phosphate. Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. Therefore, the present invention provides a method and application for producing lithium iron phosphate from hydroxy iron phosphate. This method uses ferrous sulfate as a raw material, and adds hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate, and ammonia water to synthesize hydroxy iron phosphate, thereby producing lithium iron phosphate with high press density and high capacity. In addition, this method has high production efficiency, low production cost, and is suitable for application to large-scale industrial production. [Means for solving the problem]

[0007] Therefore, in a first aspect, the first embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate. The method includes the steps of: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, purifying the ferrous sulfate solution by pressure filtration, and then obtaining an iron sulfate solution; adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution in step S2; adding hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water to the ferrous sulfate solution, reacting them for a certain period of time to form a mixed slurry; keeping the mixed slurry warm for a certain period of time, washing with water multiple times, and pressure filtration to form an iron hydroxyphosphate precursor having different iron-phosphorus ratios in step S3; flash evaporating and drying the iron hydroxyphosphate precursor in a flash evaporator, and sintering it at high temperature for a certain period of time to obtain an iron hydroxyphosphate precursor product having different iron-phosphorus ratios and different specific surface areas in step S4; and grinding the sintered material with a mechano mill and pulverizing it into a riboflavin. Step S5: by mixing the iron hydroxyphosphate with a high iron phosphorus ratio and the iron hydroxyphosphate with a low iron phosphorus ratio in a predetermined ratio, the iron hydroxyphosphate is mixed with a lithium source and an iron source in a predetermined ratio, and a certain amount of a carbon source and an additive are added to form a mixed material; Step S6: by sand milling the mixed material to obtain a nano-sized sand milling slurry, the nano-sized sand milling slurry is spray-dried to obtain a spray material; Step S8: by putting the spray material into a box furnace to sinter the material to obtain a sintered material, the sintered material is pulverized by a jet mill to obtain a pulverized material; and Step S9: by sieving the pulverized material, and by carrying out processes such as batch synthesis and packaging to obtain a lithium iron phosphate product.

[0008] Preferably, in the step S1, the mass ratio of the ferrous sulfate:the phosphorus source:the precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, the reaction time is 1 h, the phosphorus source is one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, and sodium phosphate, and the precipitant is one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, and aqueous ammonia.

[0009] Preferably, in step S2, the amount of phosphoric acid added is n(Fe):n(phosphoric acid)=1:0.15 in molar ratio. In step S3, when the iron-phosphorus supply blend ratio in the mixed slurry satisfies the iron-phosphorus molar ratio: Fe / P=1.475 to 1.490, iron hydroxyphosphate having a high iron-phosphorus ratio can be formed, and when the iron-phosphorus supply blend ratio in the mixed slurry satisfies the iron-phosphorus molar ratio: Fe / P=1.460 to 1.475, iron hydroxyphosphate having a low iron-phosphorus ratio can be produced.

[0010] Preferably, in step S3, the number of water washings is at least a plurality of times, the first water washing mainly washes off the impurities of magnesium, manganese, and sulfur, and the last water washing adds ammonia water diluted 1:1 to adjust the pH value to 6.5 to 7.0, and removes SO 4 2- The concentration of the hydrogen peroxide solution is 30% to 60%, and the mixed slurry is kept at room temperature for 3 hours.

[0011] Preferably, step S3 includes the steps of adding an excess of hydrogen peroxide water to the ferrous sulfate solution and continuing oxidation for a certain period of time; adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature to 30-40°C, then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring to mix uniformly to form an ammonium phosphate mixed solution; adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, keeping it at room temperature for a certain period of time to form a mixed slurry, washing the mixed slurry with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0012] Preferably, in step S4, the intake temperature of the flash evaporator is controlled to 220±20°C, the exhaust temperature is controlled to 110±5°C, the sintering atmosphere is air, the sintering temperature is 535-560°C, and the sintering time is 4-5 hours; in step S5, the particle size is controlled so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, the mixing frequency of the mixer is controlled to 35±2 Hz, and the mixing time is 1-2 hours.

[0013] Preferably, in step S5, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0014] Preferably, in the step S6, the molar ratio of Li:Fe:P is [1.03 to 1.04]:1:[1.03 to 1.04], the amount of the carbon source added is based on the carbon content in the final product being between 1.2% and 1.6%, the lithium source is one or more of lithium phosphate, lithium carbonate, lithium iron phosphate electrode sheet material, and lithium iron phosphate low carbon product material, the iron source is one or more of iron phosphate and iron oxide, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, the additive is one or more selected from titanium dioxide, ammonium metavanadate, and diniobium pentoxide, the doping amount is controlled to be between 300 and 3000 ppm, and the s In step S7, the sand milling particle size of the sand milling slurry is controlled between 0.45-0.75μm; in spray drying, the intake temperature is 200-220℃, the exhaust temperature is 80-110℃, the blowing frequency is 80Hz, and the spray particle size of the spray material is controlled between D50=20-40μm; in step S8, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained through natural cooling; in the grinding process, the air pressure is controlled between 0.2-0.4Mpa, the classification frequency is 80-200Hz, and the particle size of the ground material is made to satisfy D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0015] Preferably, the second embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate. The method includes the steps of: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, purifying the ferrous sulfate solution by pressure filtration, and then obtaining an iron sulfate solution; adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution in step S2; adding hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water in sequence to the ferrous sulfate solution, reacting for a certain period of time to form a mixed slurry; heating and keeping the mixed slurry at a certain period of time, washing with water multiple times, and pressure filtration to form an iron hydroxyphosphate precursor having different iron-phosphorus ratios in step S3; flash evaporating and drying the iron hydroxyphosphate precursor in a flash evaporator, and sintering it at high temperature for a certain period of time to obtain an iron hydroxyphosphate precursor product having different iron-phosphorus ratios and different specific surface areas in step S4; and grinding the sintered material with a mechano mill and mixing it with a ribbon mixer to obtain a product having different iron-phosphorus ratios and different specific surface areas in step S5. For example, step S5 can obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; step S6 can mix iron hydroxyphosphate with a high iron-phosphorus ratio and a high specific surface area with iron hydroxyphosphate with a low iron-phosphorus ratio and a low specific surface area in a predetermined ratio, and then blend with iron phosphate, lithium phosphate, and lithium carbonate in a predetermined ratio and add a certain amount of a carbon source and an additive to form a mixed material; step S7 can sand-mill the mixed material to obtain a nano-sized sand-milling slurry, and spray-dry the nano-sized sand-milling slurry to obtain a spray material; step S8 can put the spray material into a box furnace to sinter it to obtain a sintered material, and grind the sintered material with a jet mill to obtain a grinded material; and step S9 can further sieve the grinded material, and undergo processes such as batch synthesis and packaging to obtain a lithium iron phosphate product.

[0016] Preferably, step S3 includes the steps of adding an excess of hydrogen peroxide water to the ferrous sulfate solution and continuing oxidation for a certain period of time, adding a phosphoric acid solution to the oxidized ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature to 30 to 40°C, and adding the resulting solution to the oxidized ferrous sulfate solution, adding ammonia water to the ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, and forming a mixed slurry after a certain period of reaction, heating and keeping the mixed slurry at the temperature for a certain period of time, washing with water multiple times, and filtering under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios.

[0017] Preferably, the third embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate, which includes the steps of: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, purifying the ferrous sulfate solution by pressure filtration, and then purifying the ferrous sulfate solution in step S1; adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution in step S2; adding phosphoric acid, ammonium dihydrogen phosphate solution, hydrogen peroxide solution, and ammonia water in order to the ferrous sulfate solution, reacting for a certain period of time to form a mixed slurry; heating and keeping the mixed slurry at a certain period of time, washing with water multiple times, and pressure filtration to form an iron hydroxyphosphate precursor having different iron-phosphorus ratios in step S3; flash evaporating and drying the iron hydroxyphosphate precursor in a flash evaporator, and sintering the iron hydroxyphosphate precursor at high temperature for a certain period of time to obtain an iron hydroxyphosphate precursor product having different iron-phosphorus ratios and different specific surface areas in step S4; and grinding the sintered material in a mechano mill and mixing it in a ribbon mixer to obtain different iron hydroxyphosphate precursor products. Step S5 is to obtain a product of iron hydroxyphosphate having a different iron-phosphorus ratio and specific surface area; Step S6 is to mix iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a predetermined ratio, and then blend with iron oxide, lithium phosphate, lithium carbonate, and ammonium dihydrogen phosphate in a predetermined ratio, and add a certain amount of a carbon source and an additive to form a mixed material; Step S7 is to sand-mill the mixed material to obtain a nano-sized sand-milling slurry, and then spray-dry the nano-sized sand-milling slurry to obtain a spray material; Step S8 is to put the spray material into a box furnace to sinter it to obtain a sintered material, and then pulverize the sintered material with a jet mill to obtain a pulverized material; and Step S9 is to sieve the pulverized material, and then undergo processes such as batch synthesis and packaging to obtain a product of lithium iron phosphate.

[0018] Preferably, step S3 includes the steps of adding a phosphoric acid solution to the ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, adjusting the dissolution temperature to 30-40°C, and adding the resulting solution to the ferrous sulfate solution, adding an excess of hydrogen peroxide water to the ferrous sulfate solution to continue oxidizing for a certain period of time, adding ammonia water to the ferrous sulfate solution to adjust the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, heating and keeping the mixed slurry at the temperature for a certain period of time, washing with water multiple times, and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0019] Preferably, the fourth embodiment of the present invention provides a method for preparing lithium iron phosphate from iron hydroxyphosphate, which includes the steps of: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, purifying the ferrous sulfate solution by pressure filtration, and then purifying the ferrous sulfate solution in step S1; adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution in step S2; adding hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia water to the ferrous sulfate solution, reacting the mixture for a certain period of time to form a mixed slurry; keeping the mixed slurry at room temperature for a certain period of time, washing with water multiple times, and pressure filtration to form an iron hydroxyphosphate precursor having different iron-phosphorus ratios in step S3; flash evaporating and drying the iron hydroxyphosphate precursor in a flash evaporator, and sintering the iron hydroxyphosphate precursor at high temperature for a certain period of time to obtain a product of an iron hydroxyphosphate precursor having different iron-phosphorus ratios and different specific surface areas in step S4; pulverizing the sintered material in a mechano mill and mixing it in a ribbon mixer. Step S5: by mixing the iron hydroxyphosphate with the high iron phosphorus ratio and the iron hydroxyphosphate with the low iron phosphorus ratio in a predetermined ratio, the iron hydroxyphosphate with the high iron phosphorus ratio and the iron hydroxyphosphate with the low iron phosphorus ratio are mixed in a predetermined ratio, and then a certain amount of a carbon source and an additive are added to form a mixed material; Step S6: by sand milling the mixed material to obtain a nano-sized sand milling slurry, the nano-sized sand milling slurry is spray-dried to obtain a spray material; Step S8: by putting the spray material into a box furnace to sinter the material to obtain a sintered material, the sintered material is pulverized by a jet mill to obtain a pulverized material; and Step S9: by sieving the pulverized material, and by carrying out processes such as batch synthesis and packaging to obtain a lithium iron phosphate product.

[0020] Preferably, step S3 includes the steps of adding an excess of hydrogen peroxide water to the ferrous sulfate solution and continuing oxidation for a certain period of time; adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature to 30-40°C, then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing uniformly to form an ammonium phosphate mixed solution; adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, keeping the mixed slurry at room temperature for a certain period of time, washing with water multiple times, and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0021] Preferably, in the step S6, the manufacturing method of the lithium iron phosphate electrode sheet material includes the steps of crushing and sieving a waste lithium iron phosphate positive electrode sheet to separate a foil material and a raw material of the lithium iron phosphate electrode sheet material, and sintering the raw material of the lithium iron phosphate electrode sheet material in an inert atmosphere, the sintering temperature is 400-500°C, and the sintering time is 1-4 hours, and then crushing the raw material until the particle size is 1-5 μm to obtain the lithium iron phosphate electrode sheet material.

[0022] Preferably, the fifth embodiment of the present invention provides a method for preparing lithium iron phosphate from iron hydroxyphosphate, which includes the steps of: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, purifying the ferrous sulfate solution by pressure filtration, and then purifying the ferrous sulfate solution in step S1; adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to reduce the pH value of the ferrous sulfate solution in step S2; adding hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia water to the ferrous sulfate solution, reacting the mixture for a certain period of time to form a mixed slurry; keeping the mixed slurry at room temperature for a certain period of time, washing with water multiple times, and pressure filtration to form an iron hydroxyphosphate precursor having different iron-phosphorus ratios in step S3; flash evaporating and drying the iron hydroxyphosphate precursor in a flash evaporator, and sintering the iron hydroxyphosphate precursor at high temperature for a certain period of time to obtain a product of an iron hydroxyphosphate precursor having different iron-phosphorus ratios and different specific surface areas in step S4; pulverizing the sintered material with a mechano mill and mixing it with a ribbon mixer in step S5; Step S5: by mixing the iron hydroxyphosphate with the high iron phosphorus ratio and the iron hydroxyphosphate with the low iron phosphorus ratio in a predetermined ratio, the iron hydroxyphosphate with the high iron phosphorus ratio and the iron hydroxyphosphate with the low iron phosphorus ratio are mixed in a predetermined ratio, and then, lithium phosphate and lithium iron phosphate low-carbon product materials are blended in a predetermined ratio, and a certain amount of carbon source and additives are added to form a mixed material; Step S7: by sand milling the mixed material to obtain a nano-sized sand milling slurry, the nano-sized sand milling slurry is spray-dried to obtain a spray material; Step S8: by putting the spray material into a box furnace to sinter the material to obtain a sintered material, and by pulverizing the sintered material with a jet mill to obtain a pulverized material; and Step S9: by sieving the pulverized material, and by carrying out processes such as batch synthesis and packaging to obtain a lithium iron phosphate product.

[0023] Preferably, step S3 includes the steps of adding an excess of hydrogen peroxide water to the ferrous sulfate solution and continuing oxidation for a certain period of time; adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature to 30-40°C, then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing uniformly to form an ammonium phosphate mixed solution; adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, keeping the mixed slurry at room temperature for a certain period of time, washing with water multiple times, and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0024] Preferably, step S6 includes the steps of: mixing iron oxide with a phosphorus source, a lithium source, a primary carbon source and a dopant, adding water and stirring to obtain a slurry; sequentially carrying out wet grinding, spray drying, sintering under a nitrogen gas atmosphere and airflow grinding on the slurry to obtain a ground lithium iron phosphate low-carbon product material; mixing iron hydroxyphosphate with a high iron-phosphorus ratio and iron hydroxyphosphate with a low iron-phosphorus ratio in a predetermined ratio, and then blending with lithium phosphate and lithium iron phosphate low-carbon product material in a predetermined ratio, and adding a certain amount of a secondary carbon source and additives to form a mixed material.

[0025] Preferably, the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate, the lithium source is lithium carbonate and / or lithium hydroxide, the primary carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, the molar ratio of iron in the iron oxide to phosphorus in the phosphorus source is n(Fe):n(P)=(0.96-1):1, the molar ratio of lithium in the lithium source to iron in the iron oxide is n(Li):n(Fe)=(1.02-1.05):1, the dopant is a metal oxide, and the metal is selected from the group consisting of Ti, V, Nb, and Mg. the carbon content in the lithium iron phosphate low carbon product material is between 0.2% and 0.5%, the molar ratio in the mixed material is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04], the secondary carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, the amount of the primary carbon source and the secondary carbon source added is based on the carbon content in the final product being between 1.2% and 1.6%, and the additive is one or more selected from titanium dioxide, ammonium metavanadate, and diniobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0026] In a second aspect, embodiments of the present invention provide a lithium-ion battery cathode material processed in a method for producing lithium iron phosphate from iron hydroxyphosphate provided in the first aspect above.

[0027] In a third aspect, embodiments of the present invention provide a lithium-ion battery comprising the lithium-ion battery cathode material according to the second aspect above. Effect of the Invention

[0028] The method for producing lithium iron phosphate from iron hydroxyphosphate according to the embodiment of the present invention uses ferrous sulfate, which is a by-product of titanium white, to produce iron sulfate, and then adds other materials to react to produce iron hydroxyphosphates with different iron-phosphorus ratios, and then undergoes different sintering processes to obtain iron hydroxyphosphate products with high iron-phosphorus ratios and high specific surface areas, and iron hydroxyphosphate products with low iron-phosphorus ratios and low specific surface areas. Iron hydroxyphosphate with high iron-phosphorus ratios and high specific surface areas and iron hydroxyphosphate with low iron-phosphorus ratios and low specific surface areas are mixed, and then mixed with a lithium source and an iron source in a predetermined ratio, and then a carbon source and additives are added to form a mixed material, and the mixed material is subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain a lithium iron phosphate product. The method mixes and combines iron hydroxyphosphate with high iron-phosphorus ratio and iron hydroxyphosphate with low iron-phosphorus ratio, and mixes and combines the two kinds of iron hydroxyphosphates to form a combination of large particles and small particles, which helps to improve the press density of the lithium iron phosphate material and improve the electrochemical performance. In addition, the method requires a low reaction temperature, a short reaction time, low equipment requirements, a simple process flow, and improves production efficiency, making it suitable for large-scale industrial production. [Brief description of the drawings]

[0029] [Figure 1] 1 is a flowchart of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a first embodiment of the present invention. [Diagram 2] 4 is a flowchart of an example of step S3 of the method for producing lithium iron phosphate from iron hydroxyphosphate according to the first embodiment of the present invention. [Diagram 3] 4 is a flowchart of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a second embodiment of the present invention. [Figure 4] 10 is a flowchart of an example of step S3 of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a second embodiment of the present invention. [Diagram 5]1 is a flowchart of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a third embodiment of the present invention. [Figure 6] 10 is a flowchart of an example of step S3 of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a third embodiment of the present invention. [Figure 7] 10 is a flowchart of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a fourth embodiment of the present invention. [Figure 8] 10 is a flowchart of an example of step S3 of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a fourth embodiment of the present invention. [Figure 9] 5 is a flowchart of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a fifth embodiment of the present invention. [Figure 10] 13 is a flowchart of an example of step S3 of a method for producing lithium iron phosphate from iron hydroxyphosphate according to a fifth embodiment of the present invention. [Figure 11] 13 is a flowchart of step S6 for producing lithium iron phosphate from iron hydroxyphosphate according to a fifth embodiment of the present invention. [Figure 12] FIG. 2 is a SEM spectrum of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 1 of the present invention. [Figure 13] FIG. 2 is a SEM spectrum of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention. [Figure 14] FIG. 2 is an XRD spectrum diagram of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 1 of the present invention. [Figure 15] FIG. 2 is an XRD spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention. [Figure 16] FIG. 2 is a SEM spectrum of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 2 of the present invention. [Figure 17] FIG. 2 is a SEM spectrum of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention. [Figure 18]FIG. 2 is an XRD spectrum diagram of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 2 of the present invention. [Figure 19] FIG. 2 is an XRD spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention. [Figure 20] FIG. 2 is a SEM spectrum of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 3 of the present invention. [Figure 21] FIG. 2 is a SEM spectrum of the lithium iron phosphate positive electrode material prepared in Example 3 of the present invention. [Figure 22] FIG. 2 is an XRD spectrum diagram of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 3 of the present invention. [Diagram 23] FIG. 2 is an XRD spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 3 of the present invention. [Figure 24] FIG. 1 is a SEM spectrum of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 4 of the present invention. [Diagram 25] FIG. 1 is a SEM spectrum of the lithium iron phosphate positive electrode material prepared in Example 4 of the present invention. [Figure 26] FIG. 1 is an XRD spectrum diagram of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 4 of the present invention. [Figure 27] FIG. 4 is an XRD spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 4 of the present invention. [Figure 28] FIG. 1 is a SEM spectrum of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 5 of the present invention. [Figure 29] FIG. 1 is a SEM spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 5 of the present invention. [Diagram 30] FIG. 1 is an XRD spectrum diagram of iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 5 of the present invention. [Diagram 31] FIG. 1 is an XRD spectrum diagram of the lithium iron phosphate positive electrode material prepared in Example 5 of the present invention. [Diagram 32]2 is a charge / discharge curve (0.1C) of a button-type half cell assembled with the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention; [Diagram 33] 2 is a charge / discharge curve (1C) of a button-type half cell assembled with the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the embodiments of the present invention will be described in detail, and examples of the embodiments are shown in the drawings, and the same or similar reference numerals throughout indicate the same or similar parts or parts having the same or similar functions. The embodiments described below with reference to the drawings are illustrative and are for interpreting the present invention, but should not be understood as limiting the present invention.

[0031] The following disclosure provides many different embodiments or examples for realizing different structures of the present invention. In order to simplify the disclosure of the present invention, the following describes specific example components and installations. It should be understood that these are merely illustrative and are not intended to limit the present invention. The present invention may also use repeated reference numerals and / or alphabetical references in different examples. The present invention may also use repeated reference numerals and / or alphabetical references in different examples, and such repetition is for the purpose of brevity and clarity and does not itself indicate a relationship between the various embodiments and / or installations described. The present invention also provides examples of various specific processes and materials, but those skilled in the art may recognize the applicability of other processes and / or the use of other materials.

[0032] A first embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate in order to produce lithium iron phosphate with high press density and high capacity. As shown in Fig. 1, the method includes the following steps S1 to S9.

[0033] In step S1, ferrous sulfate, a by-product of titanium white, is added to a phosphorus source and a precipitant for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0034] The mass ratio of ferrous sulfate:phosphorus source:precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, and the reaction time is 1 hour.

[0035] In this embodiment, the phosphorus source may be one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, sodium phosphate, etc., and the precipitant may be one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, aqueous ammonia, etc.

[0036] In step S2, an appropriate amount of phosphoric acid is added to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution.

[0037] The amount of phosphoric acid added was n(Fe):n(phosphoric acid)=1:0.15 in molar ratio.

[0038] In step S3, hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water are added to the ferrous sulfate solution, and then reacted for a certain period of time to form a mixed slurry. The mixed slurry is then kept at room temperature for a certain period of time, and then washed with water multiple times and pressure filtered to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0039] When the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.475 to 1.490, iron hydroxyphosphate with a high iron / phosphorus ratio can be formed, and when the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.460 to 1.475, iron hydroxyphosphate with a low iron / phosphorus ratio can be produced.

[0040] In this embodiment, the concentration of the hydrogen peroxide solution is between 30% and 60%, and the mixed slurry is kept at room temperature for 3 hours. The number of times of washing with water may be multiple times. In the first washing with water, mainly impurities such as magnesium, manganese, and sulfur are washed away, and in the last washing with water, ammonia water diluted 1:1 is added to adjust the pH value to 6.5 to 7.0, and SO 4 2- Specifically, the number of washings may be three, of which the first and second washings are mainly for washing out impurities such as manganese, magnesium, and sulfur, and in the third washing, ammonia water diluted 1:1 is added to adjust the pH value to 6.5-7.0 and remove SO 4 2- Wash away the ions.

[0041] Specifically, in this embodiment, as shown in FIG. 2, step S3 is Step S311 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S312 of adding water to ammonium dihydrogen phosphate powder to dissolve it and prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40°C. Then, phosphoric acid solution and ammonia water are added to the ammonium dihydrogen phosphate solution and stirred uniformly to form an ammonium phosphate mixed solution; and step S313 of adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then keeping the mixed slurry at room temperature for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0042] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry, and then sintered at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas.

[0043] The iron hydroxyphosphate precursor is flash evaporated and dried in order to remove free water, and the intake temperature of the flash evaporator is controlled to 220±20°C and the exhaust temperature to 110±5°C. The sintering atmosphere may be air, the sintering temperature may be 535-560°C, and the sintering time may be 4-5 hours.

[0044] In step S5, the sintered material is ground in a mechano mill and mixed in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas.

[0045] In the grinding process, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm. The mixing frequency of the mixer may be controlled to 35±2 Hz, and the mixing time may be 1-2 hours.

[0046] In this embodiment, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0047] In step S6, iron hydroxyphosphate having a high iron-phosphorus ratio and iron hydroxyphosphate having a low iron-phosphorus ratio are mixed in a predetermined ratio, and then a lithium source and an iron source are blended in a predetermined ratio, and a certain amount of a carbon source and an additive are added to form a mixed material.

[0048] In this embodiment, the ratio of the iron hydroxyphosphate with a high iron phosphorus ratio to the iron hydroxyphosphate with a low iron phosphorus ratio is between 2:8 and 8:2, and preferably the ratio of the iron hydroxyphosphate with a high iron phosphorus ratio to the iron hydroxyphosphate with a low iron phosphorus ratio is 3:7. In addition, in the mixed material, the molar ratio is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]. The lithium source may be one or more of lithium phosphate, lithium carbonate, lithium iron phosphate electrode sheet material, and lithium iron phosphate low carbon product material, and the iron source may be one or more of iron phosphate and iron oxide, and the amount of the carbon source added is based on the carbon content in the final product being between 1.2% and 1.6%.

[0049] In this embodiment, the carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, and the additive may be one or more selected from titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0050] In step S7, the mixed material is sand-milled to obtain a nano-sized sand-milled slurry, and the nano-sized sand-milled slurry is spray-dried to obtain a spray material.

[0051] The sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm. In the spray drying, the intake temperature may be 200 to 220° C., the exhaust temperature may be 80 to 110° C., and the blowing frequency may be 80 Hz, and the spray particle size in the finally formed spray material is controlled to be between D50=20 to 40 μm.

[0052] In step S8, the sprayed material is put into a box furnace and sintered to obtain a sintered material, and the sintered material is pulverized in a jet mill to obtain a pulverized material.

[0053] In the sintering process, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained after natural cooling. In the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the classification frequency is 80-200Hz, so that the particle size of the finally obtained crushed material satisfies D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0054] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0055] The method for producing lithium iron phosphate from iron hydroxyphosphate according to the first embodiment of the present invention uses ferrous sulfate, a by-product of titanium white, to produce iron sulfate, which is then reacted with other materials to produce iron hydroxyphosphate precursors with different iron-phosphorus ratios. Then, through different sintering processes, iron hydroxyphosphate products with high iron-phosphorus ratios and high specific surface areas and iron hydroxyphosphate products with low iron-phosphorus ratios and low specific surface areas are obtained. Compared with iron phosphate produced by the conventional method, the iron hydroxyphosphate produced by this method does not have a crystal transition synthesis step at 80-90°C and belongs to a spherical small particle amorphous precursor. In the water washing, separation and purification step, impurities are less likely to be occluded inside the crystals, and after multiple water washings, the impurities Mn, Mg, SO 4 2- Since impurities such as ions are washed out, the impurity content of the iron hydroxyphosphate product is low and the purity of the product is high. In addition, the iron phosphorus ratio and specific surface area of ​​the iron hydroxyphosphate produced by this method can be adjusted, and iron hydroxyphosphate with different iron phosphorus ratios can be produced as needed. Iron hydroxyphosphate with a high iron phosphorus ratio and high specific surface area has small particles and can improve the discharge capacity of the material. Iron hydroxyphosphate with a low iron phosphorus ratio and low specific surface area has large particles and can improve the press density of the material, which is more conducive to the construction of the crystal structure of the subsequent lithium iron phosphate.

[0056] In the subsequent step, the method includes mixing the iron hydroxyphosphate having a high iron phosphorus ratio and a high specific surface area with the iron hydroxyphosphate having a low iron phosphorus ratio and a low specific surface area, and then mixing with a lithium source and an iron source in a predetermined ratio, and then adding a carbon source and additives to form a mixed material, and the mixed material is subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain a lithium iron phosphate product. The method includes mixing and combining the iron hydroxyphosphate having a high iron phosphorus ratio and the iron hydroxyphosphate having a low iron phosphorus ratio to form a combination of large particles and small particles, which is helpful in improving the press density of the lithium iron phosphate material and improving the electrochemical performance. In addition, the method requires a low reaction temperature, a short reaction time, low requirements for equipment, and a simple process flow, which improves the production efficiency and is suitable for large-scale industrial production.

[0057] A second embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate in order to produce lithium iron phosphate with high press density and high capacity. As shown in Fig. 3, the method includes the following steps S1 to S9.

[0058] In step S1, ferrous sulfate, a by-product of titanium white, is added to a phosphorus source and a precipitant for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0059] The mass ratio of ferrous sulfate:phosphorus source:precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, and the reaction time is 1 hour.

[0060] In this embodiment, the phosphorus source may be one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, sodium phosphate, etc., and the precipitant may be one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, aqueous ammonia, etc.

[0061] In step S2, an appropriate amount of phosphoric acid is added to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution.

[0062] The amount of phosphoric acid added was n(Fe):n(phosphoric acid)=1:0.15 in molar ratio.

[0063] In step S3, hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water are added to the ferrous sulfate solution in this order, and then reacted for a certain period of time to form a mixed slurry. The mixed slurry is heated and kept at that temperature for a certain period of time, and then washed with water multiple times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios.

[0064] In this embodiment, hydrogen peroxide is first added to sufficiently oxidize the divalent iron ions to completely convert them to trivalent iron ions, and then phosphoric acid and ammonium dihydrogen phosphate are added to adjust the solution ions to an appropriate iron-phosphorus molar ratio, thereby making the generated iron hydroxyphosphate precursor more stable and also making the particles of the generated iron hydroxyphosphate precursor larger, making it easier to filter and wash under pressure.

[0065] When the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.475 to 1.490, iron hydroxyphosphate with a high iron / phosphorus ratio can be formed, and when the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.460 to 1.475, iron hydroxyphosphate with a low iron / phosphorus ratio can be produced.

[0066] In this embodiment, the concentration of the hydrogen peroxide solution is between 30% and 60%, and the mixed slurry is heated to 60 to 80° C. and then kept at 60 to 80° C. for 3 hours. The number of times of washing with water may be multiple times. In the first washing with water, mainly impurities such as magnesium, manganese, and sulfur are washed away, and in the last washing with water, ammonia water diluted 1:1 is added to adjust the pH value to 6.5 to 7.0, and SO 4 2-Specifically, the number of washings may be three, of which the first and second washings are mainly for washing out impurities such as manganese, magnesium, and sulfur, and in the third washing, ammonia water diluted 1:1 is added to adjust the pH value to 6.5-7.0 and remove SO 4 2- Wash away the ions.

[0067] Specifically, in this embodiment, as shown in FIG. 4, step S3 is Step S321 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S322: adding phosphoric acid solution to the oxidized ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, dissolving it at a temperature of 30 to 40°C, and adding the resulting solution to the oxidized ferrous sulfate solution; and step S323 of adding ammonia water to the ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, heating and keeping the mixed slurry for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0068] The mixed slurry is heated to a temperature of 60 to 80° C. and kept at that temperature for 3 hours.

[0069] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry, and then sintered at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas.

[0070] The iron hydroxyphosphate precursor is flash evaporated and dried in order to remove free water, and the intake temperature of the flash evaporator is controlled to 220±20°C and the exhaust temperature to 110±5°C. The sintering atmosphere may be air, the sintering temperature may be 535-560°C, and the sintering time may be 4-5 hours.

[0071] In step S5, the sintered material is ground in a mechano mill and mixed in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas.

[0072] In the grinding process, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm. The mixing frequency of the mixer may be controlled to 35±2 Hz, and the mixing time may be 1-2 hours.

[0073] In this embodiment, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0074] In step S6, iron hydroxyphosphate having a high iron-phosphorus ratio and iron hydroxyphosphate having a low iron-phosphorus ratio are mixed in a predetermined ratio, and then blended with iron phosphate, lithium phosphate, and lithium carbonate in a predetermined ratio, and a certain amount of a carbon source and an additive are added to form a mixed material.

[0075] In this embodiment, the ratio of iron hydroxyphosphate with a high iron phosphorus ratio to iron hydroxyphosphate with a low iron phosphorus ratio is between 2:8 and 8:2, and preferably the ratio of iron hydroxyphosphate with a high iron phosphorus ratio to iron hydroxyphosphate with a low iron phosphorus ratio is 3:7. In addition, the molar ratio of the mixed material is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]. The amount of the carbon source added is based on the carbon content of the final product being between 1.2% and 1.6%.

[0076] In this embodiment, the carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, and the additive may be one or more selected from titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0077] In step S7, the mixed material is sand-milled to obtain a nano-sized sand-milled slurry, and the nano-sized sand-milled slurry is spray-dried to obtain a spray material.

[0078] The sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm. In the spray drying, the intake temperature may be 200 to 220° C., the exhaust temperature may be 80 to 110° C., and the blowing frequency may be 80 Hz, and the spray particle size in the finally formed spray material is controlled to be between D50=20 to 40 μm.

[0079] In step S8, the sprayed material is put into a box furnace and sintered to obtain a sintered material, and the sintered material is pulverized in a jet mill to obtain a pulverized material.

[0080] In the sintering process, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained after natural cooling. In the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the classification frequency is 80-200Hz, so that the particle size of the finally obtained crushed material satisfies D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0081] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0082] In the method for producing lithium iron phosphate from iron hydroxyphosphate according to the second embodiment of the present invention, hydrogen peroxide is first added to the iron hydroxyphosphate produced by this method to fully oxidize the divalent iron ions to completely convert them into trivalent iron ions, and then phosphoric acid and ammonium dihydrogen phosphate are added to adjust the solution ions to a suitable molar ratio of iron to phosphorus, thereby making the generated iron hydroxyphosphate precursor more stable, and the particles of the generated iron hydroxyphosphate precursor are made larger by heating the mixed slurry and then keeping it warm, which makes it easier to filter and wash under pressure. In addition, iron hydroxyphosphate with a high iron-phosphorus ratio and iron hydroxyphosphate with a low iron-phosphorus ratio are mixed, and then mixed with iron phosphate, lithium phosphate, and lithium carbonate in a predetermined ratio, and additives are added to form a mixed material, which can then be subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain a lithium iron phosphate product. The method combines iron hydroxyphosphate with a high iron phosphorus ratio and iron hydroxyphosphate with a low iron phosphorus ratio, and introduces three materials, i.e., iron phosphate, lithium phosphate, and lithium carbonate. The introduction of iron phosphate and lithium carbonate facilitates reducing the agglomeration of lithium iron phosphate particles and improving the circularity of lithium iron phosphate particles, thereby improving the press density and electrochemical performance of the lithium iron phosphate material.

[0083] A third embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate in order to produce lithium iron phosphate with high press density and high capacity. As shown in Fig. 5, the method includes the following steps S1 to S9.

[0084] In step S1, ferrous sulfate, a by-product of titanium white, is added to a phosphorus source and a precipitant for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0085] The mass ratio of ferrous sulfate:phosphorus source:precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, and the reaction time is 1 hour.

[0086] In this embodiment, the phosphorus source may be one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, sodium phosphate, etc., and the precipitant may be one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, aqueous ammonia, etc.

[0087] In step S2, an appropriate amount of phosphoric acid is added to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution.

[0088] The amount of phosphoric acid added was n(Fe):n(phosphoric acid)=1:0.15 in molar ratio.

[0089] In step S3, phosphoric acid, ammonium dihydrogen phosphate solution, hydrogen peroxide solution, and ammonia water are added to the ferrous sulfate solution in this order, and then reacted for a certain period of time to form a mixed slurry. The mixed slurry is heated and kept at the temperature for a certain period of time, and then washed with water multiple times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios.

[0090] In this embodiment, phosphoric acid and ammonium dihydrogen phosphate are first added to adjust the solution ions to an appropriate iron phosphorus molar ratio, and then hydrogen peroxide is added to fully oxidize the divalent iron ions to completely convert them to trivalent iron ions, thereby making the generated iron hydroxyphosphate precursor more stable and making the particles of the generated iron hydroxyphosphate precursor larger, making it easier to filter and wash under pressure. When the iron phosphorus supply blend ratio in the mixed slurry satisfies the iron phosphorus molar ratio: Fe / P = 1.475 to 1.490, iron hydroxyphosphate with a high iron phosphorus ratio can be formed, and when the iron phosphorus supply blend ratio in the mixed slurry satisfies the iron phosphorus molar ratio: Fe / P = 1.460 to 1.475, iron hydroxyphosphate with a low iron phosphorus ratio can be produced.

[0091] In this embodiment, the concentration of the hydrogen peroxide solution is between 30% and 60%, and the mixed slurry is heated to 60 to 80° C. and then kept at 60 to 80° C. for 3 hours. The number of times of washing with water may be multiple times. In the first washing with water, mainly impurities such as magnesium, manganese, and sulfur are washed away, and in the last washing with water, ammonia water diluted 1:1 is added to adjust the pH value to 6.5 to 7.0, and SO 4 2- Specifically, the number of washings may be three, of which the first and second washings are mainly for washing out impurities such as manganese, magnesium, and sulfur, and in the third washing, ammonia water diluted 1:1 is added to adjust the pH value to 6.5-7.0 and remove SO 4 2- Wash away the ions.

[0092] Specifically, in this embodiment, as shown in FIG. 6, step S3 is Step S331: adding phosphoric acid solution to ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare ammonium dihydrogen phosphate solution with a concentration of 30%, dissolving it at a temperature of 30 to 40°C, and adding it to the ferrous sulfate solution; Step S332 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; and step S333 of adding ammonia water to the ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, heating and keeping the mixed slurry for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0093] The mixed slurry is heated to a temperature of 60 to 80° C. and kept at that temperature for 3 hours.

[0094] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry, and then sintered at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas.

[0095] The iron hydroxyphosphate precursor is flash evaporated and dried in order to remove free water, and the intake temperature of the flash evaporator is controlled to 220±20°C and the exhaust temperature to 110±5°C. The sintering atmosphere may be air, the sintering temperature may be 535-560°C, and the sintering time may be 4-5 hours.

[0096] In step S5, the sintered material is ground in a mechano mill and mixed in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas.

[0097] In the grinding process, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm. The mixing frequency of the mixer may be controlled to 35±2 Hz, and the mixing time may be 1-2 hours.

[0098] In this embodiment, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0099] In step S6, iron hydroxyphosphate with a high iron-phosphorus ratio and iron hydroxyphosphate with a low iron-phosphorus ratio are mixed in a predetermined ratio, and then blended with iron oxide, lithium phosphate, lithium carbonate, and ammonium dihydrogen phosphate in a predetermined ratio, and a certain amount of a carbon source and an additive are added to form a mixed material.

[0100] In this embodiment, the ratio of iron hydroxyphosphate with a high iron phosphorus ratio to iron hydroxyphosphate with a low iron phosphorus ratio is between 2:8 and 8:2, and preferably the ratio of iron hydroxyphosphate with a high iron phosphorus ratio to iron hydroxyphosphate with a low iron phosphorus ratio is 3:7. In addition, the molar ratio of the mixed material is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]. The amount of the carbon source added is based on the carbon content of the final product being between 1.2% and 1.6%.

[0101] In this embodiment, the carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, and the additive may be one or more selected from titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0102] In step S7, the mixed material is sand-milled to obtain a nano-sized sand-milled slurry, and the nano-sized sand-milled slurry is spray-dried to obtain a spray material.

[0103] The sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm. In the spray drying, the intake temperature may be 200 to 220° C., the exhaust temperature may be 80 to 110° C., and the blowing frequency may be 80 Hz, and the spray particle size in the finally formed spray material is controlled to be between D50=20 to 40 μm.

[0104] In step S8, the sprayed material is put into a box furnace and sintered to obtain a sintered material, and the sintered material is pulverized in a jet mill to obtain a pulverized material.

[0105] In the sintering process, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained after natural cooling. In the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the classification frequency is 80-200Hz, so that the particle size of the finally obtained crushed material satisfies D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0106] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0107] The method for producing lithium iron phosphate from hydroxy iron phosphate according to the third embodiment of the present invention includes mixing hydroxy iron phosphate with a high iron phosphorus ratio and hydroxy iron phosphate with a low iron phosphorus ratio, then mixing with iron oxide, lithium phosphate, lithium carbonate and ammonium dihydrogen phosphate in a predetermined ratio, adding additives to form a mixed material, and then the mixed material is subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis and packaging to obtain a lithium iron phosphate product. This method mixes and combines hydroxy iron phosphate with a high iron phosphorus ratio and hydroxy iron phosphate with a low iron phosphorus ratio, and introduces four materials, namely, iron oxide, lithium phosphate, lithium carbonate and ammonium dihydrogen phosphate. The addition of iron oxide and ammonium dihydrogen phosphate can effectively reduce the cost of materials, improve the viscosity of the subsequent sand milling slurry, and improve the stability of the slurry. In addition, the primary particles of the iron oxide raw material are small, and the particles of the product lithium iron phosphate are small, which effectively improves the rate performance. As a phosphorus source, ammonium dihydrogen phosphate is easy to increase the amount of gas generation and reduce particle aggregation.

[0108] A fourth embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate in order to produce lithium iron phosphate with high press density and high capacity. As shown in Fig. 7, the method includes the following steps S1 to S9.

[0109] In step S1, ferrous sulfate, a by-product of titanium white, is added to a phosphorus source and a precipitant for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0110] The mass ratio of ferrous sulfate:phosphorus source:precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, and the reaction time is 1 hour.

[0111] In this embodiment, the phosphorus source may be one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, sodium phosphate, etc., and the precipitant may be one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, aqueous ammonia, etc.

[0112] In step S2, an appropriate amount of phosphoric acid is added to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution.

[0113] The amount of phosphoric acid added was n(Fe):n(phosphoric acid)=1:0.15 in molar ratio.

[0114] In step S3, hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water are added to the ferrous sulfate solution, and then reacted for a certain period of time to form a mixed slurry. The mixed slurry is then kept at room temperature for a certain period of time, and then washed with water multiple times and pressure filtered to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0115] When the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.475 to 1.490, iron hydroxyphosphate with a high iron / phosphorus ratio can be formed, and when the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.460 to 1.475, iron hydroxyphosphate with a low iron / phosphorus ratio can be produced.

[0116] In this embodiment, the concentration of the hydrogen peroxide solution is between 30% and 60%, and the mixed slurry is kept at room temperature for 3 hours. The number of times of washing with water may be multiple times. In the first washing with water, mainly impurities such as magnesium, manganese, and sulfur are washed away, and in the last washing with water, ammonia water diluted 1:1 is added to adjust the pH value to 6.5 to 7.0, and SO 4 2- Specifically, the number of washings may be three, of which the first and second washings are mainly for washing out impurities such as manganese, magnesium, and sulfur, and in the third washing, ammonia water diluted 1:1 is added to adjust the pH value to 6.5-7.0 and remove SO 4 2- Wash away the ions.

[0117] Specifically, in this embodiment, as shown in FIG. 8, step S3 is Step S341 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S342: adding water to the ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40°C; then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing them uniformly to form an ammonium phosphate mixed solution; and step S343 of adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, and reacting for a certain period of time to form a mixed slurry. The mixed slurry is kept at room temperature for a certain period of time, and then washed with water multiple times and pressure filtered to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0118] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry, and then sintered at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas.

[0119] The iron hydroxyphosphate precursor is flash evaporated and dried in order to remove free water, and the intake temperature of the flash evaporator is controlled to 220±20°C and the exhaust temperature to 110±5°C. The sintering atmosphere may be air, the sintering temperature may be 535-560°C, and the sintering time may be 4-5 hours.

[0120] In step S5, the sintered material is ground in a mechano mill and mixed in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas.

[0121] In the grinding process, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm. The mixing frequency of the mixer may be controlled to 35±2 Hz, and the mixing time may be 1-2 hours.

[0122] In this embodiment, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0123] In step S6, the iron hydroxyphosphate having a high iron-phosphorus ratio and the iron hydroxyphosphate having a low iron-phosphorus ratio are mixed in a predetermined ratio, and then blended with the lithium phosphate and lithium iron phosphate electrode sheet materials in a predetermined ratio, and a certain amount of a carbon source and an additive are added to form a mixed material.

[0124] Preferably, the lithium iron phosphate electrode sheet material can be manufactured using recycled lithium iron phosphate waste positive electrode sheets to reduce material costs. Specifically, the lithium iron phosphate electrode sheet material can be manufactured by the following method. The waste lithium iron phosphate positive electrode sheets are crushed and sieved to separate the foil material and the raw material of the lithium iron phosphate electrode sheet material, and the raw material of the lithium iron phosphate electrode sheet material is sintered in an inert atmosphere, with the sintering temperature being 400-500°C and the sintering time being 1-4 hours, and then crushed until the particle size is 1-5 μm to obtain the lithium iron phosphate electrode sheet material.

[0125] In this embodiment, the ratio of the iron hydroxyphosphate with a high iron phosphorus ratio to the iron hydroxyphosphate with a low iron phosphorus ratio is between 2:8 and 8:2, and preferably the ratio of the iron hydroxyphosphate with a high iron phosphorus ratio to the iron hydroxyphosphate with a low iron phosphorus ratio is 3:7. In addition, the molar ratio of the mixed material is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]. In this embodiment, the amount of the carbon source added is based on the carbon content of the final product being between 1.2% and 1.6%.

[0126] In this embodiment, the carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, and the additive may be one or more selected from titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0127] In step S7, the mixed material is sand-milled to obtain a nano-sized sand-milled slurry, and the nano-sized sand-milled slurry is spray-dried to obtain a spray material.

[0128] The sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm. In the spray drying, the intake temperature may be 200 to 220° C., the exhaust temperature may be 80 to 110° C., and the blowing frequency may be 80 Hz, and the spray particle size in the finally formed spray material is controlled to be between D50=20 to 40 μm.

[0129] In step S8, the sprayed material is put into a box furnace and sintered to obtain a sintered material, and the sintered material is pulverized in a jet mill to obtain a pulverized material.

[0130] In the sintering process, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained after natural cooling. In the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the classification frequency is 80-200Hz, so that the particle size of the finally obtained crushed material satisfies D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0131] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0132] The method for producing lithium iron phosphate from hydroxyiron phosphate according to the fourth embodiment of the present invention includes mixing hydroxyiron phosphate with a high iron phosphorus ratio and hydroxyiron phosphate with a low iron phosphorus ratio, mixing with lithium phosphate and lithium iron phosphate electrode sheet material in a predetermined ratio, adding a carbon source and additives to form a mixed material, and then the mixed material is subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain lithium iron phosphate products. This method combines hydroxyiron phosphate with a high iron phosphorus ratio and hydroxyiron phosphate with a low iron phosphorus ratio, and introduces lithium phosphate and a lithium iron phosphate electrode sheet material produced from recycled waste lithium iron phosphate positive electrode sheet material, so that the recycled lithium iron phosphate electrode sheet material can greatly reduce the cost of materials and can recycle and reuse the waste lithium iron phosphate electrode sheet material. In the sintering process, the lithium iron phosphate electrode sheet material provides steric hindrance, which helps to reduce the aggregation of lithium iron phosphate particles and improve the circularity of lithium iron phosphate particles, thereby improving the press density and electrochemical performance of the lithium iron phosphate material.

[0133] A fifth embodiment of the present invention provides a method for producing lithium iron phosphate from iron hydroxyphosphate in order to produce lithium iron phosphate with high press density and high capacity. As shown in Fig. 9, the method includes the following steps S1 to S9.

[0134] In step S1, ferrous sulfate, a by-product of titanium white, is added to a phosphorus source and a precipitant for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0135] The mass ratio of ferrous sulfate:phosphorus source:precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, and the reaction time is 1 hour.

[0136] In this embodiment, the phosphorus source may be one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, sodium phosphate, etc., and the precipitant may be one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, aqueous ammonia, etc.

[0137] In step S2, an appropriate amount of phosphoric acid is added to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution.

[0138] The amount of phosphoric acid added was n(Fe):n(phosphoric acid)=1:0.15 in molar ratio.

[0139] In step S3, hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water are added to the ferrous sulfate solution, and then reacted for a certain period of time to form a mixed slurry. The mixed slurry is then kept at room temperature for a certain period of time, and then washed with water multiple times and pressure filtered to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0140] When the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.475 to 1.490, iron hydroxyphosphate with a high iron / phosphorus ratio can be formed, and when the iron / phosphorus supply blend ratio in the mixed slurry satisfies the iron / phosphorus molar ratio: Fe / P = 1.460 to 1.475, iron hydroxyphosphate with a low iron / phosphorus ratio can be produced.

[0141] In this embodiment, the concentration of the hydrogen peroxide solution is between 30% and 60%, and the incubation time is 3 hours. The number of times of washing with water may be multiple times. In the first washing with water, mainly impurities such as magnesium, manganese, and sulfur are washed away, and in the last washing with water, ammonia water diluted 1:1 is added to adjust the pH value to 6.5 to 7.0, and SO 4 2-Specifically, the number of washings may be three, of which the first and second washings are mainly for washing out impurities such as manganese, magnesium, and sulfur, and in the third washing, ammonia water diluted 1:1 is added to adjust the pH value to 6.5-7.0 and remove SO 4 2- Wash away the ions.

[0142] Specifically, in this embodiment, as shown in FIG. 10, step S3 is Step S351 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S352: adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40°C; then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing them uniformly to form an ammonium phosphate mixed solution; and step S353 of adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then keeping the mixed slurry at room temperature for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0143] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry, and then sintered at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas.

[0144] The iron hydroxyphosphate precursor is flash evaporated and dried in order to remove free water, and the intake temperature of the flash evaporator is controlled to 220±20°C and the exhaust temperature to 110±5°C. The sintering atmosphere may be air, the sintering temperature may be 535-560°C, and the sintering time may be 4-5 hours.

[0145] In step S5, the sintered material is ground in a mechano mill and mixed in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas.

[0146] In the grinding process, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm. The mixing frequency of the mixer may be controlled to 35±2 Hz, and the mixing time may be 1-2 hours.

[0147] In this embodiment, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area satisfies BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio satisfies Fe / P=1.440-1.460 and has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440-1.460 and the specific surface area satisfies BET=5-10 m 2 Meets / g.

[0148] In step S6, the iron hydroxyphosphate with a high iron-phosphorus ratio and the iron hydroxyphosphate with a low iron-phosphorus ratio are mixed in a predetermined ratio, and then blended with lithium phosphate and lithium iron phosphate low-carbon product materials in a predetermined ratio, and a certain amount of carbon source and additives are added to form a mixed material.

[0149] In this embodiment, the carbon content in the lithium iron phosphate low carbon product material is between 0.2% and 0.5%. Specifically, in this embodiment, as shown in FIG. 11, the step S6 includes the following steps S61 to S63.

[0150] In step S61, iron oxide is mixed with a phosphorus source, a lithium source, a primary carbon source and a dopant to obtain a mixed material, and then water is added and stirred to obtain a slurry.

[0151] The phosphorus source may be one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate, the lithium source may be lithium carbonate and / or lithium hydroxide, the primary carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, the molar ratio of iron in the iron oxide to phosphorus in the phosphorus source is n(Fe):n(P)=(0.96-1):1, and the molar ratio of lithium in the lithium source to iron in the iron oxide is n(Li):n(Fe)=(1.02-1.05):1. The dopant is a metal oxide, and the metal is at least one of Ti, V, Nb, and Mg.

[0152] In step S62, the slurry is successively subjected to wet grinding, spray drying, sintering under a nitrogen gas atmosphere, and airflow pulverization to obtain a pulverized lithium iron phosphate low-carbon product material.

[0153] The sintering temperature is 500 to 600° C., the sintering time is 6 to 10 hours, and the sintering pressure is 50 to 200 Pa.

[0154] In step S63, the iron hydroxyphosphate with a high iron-phosphorus ratio and the iron hydroxyphosphate with a low iron-phosphorus ratio are mixed in a predetermined ratio, and then blended with the lithium phosphate and lithium iron phosphate low-carbon product materials in a predetermined ratio, and a certain amount of secondary carbon source and additives are added to form a mixed material.

[0155] Preferably, the ratio of the iron hydroxyphosphate having a high iron phosphorus ratio to the iron hydroxyphosphate having a low iron phosphorus ratio is between 2:8 and 8:2, and preferably, the ratio of the iron hydroxyphosphate having a high iron phosphorus ratio to the iron hydroxyphosphate having a low iron phosphorus ratio satisfies 3:7. Also, in the mixed material, the molar ratio is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].

[0156] In this embodiment, the secondary carbon source may be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, and the amount of the primary carbon source and the secondary carbon source added is based on the carbon content of the final product being between 1.2% and 1.6%. The additive may be one or more selected from titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm.

[0157] In step S7, the mixed material is sand-milled to obtain a nano-sized sand-milled slurry, and the nano-sized sand-milled slurry is spray-dried to obtain a spray material.

[0158] The sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm. In the spray drying, the intake temperature may be 200 to 220° C., the exhaust temperature may be 80 to 110° C., and the blowing frequency may be 80 Hz, and the spray particle size in the finally formed spray material is controlled to be between D50=20 to 40 μm.

[0159] In step S8, the sprayed material is put into a box furnace and sintered to obtain a sintered material, and the sintered material is pulverized in a jet mill to obtain a pulverized material.

[0160] In the sintering process, the sintering atmosphere is nitrogen gas, the sintering temperature is 750-780℃, the heating rate is 3℃ / min, the sintering time is 8-12h, and then the sintered material is obtained after natural cooling. In the crushing process, the air pressure is controlled between 0.2-0.4Mpa, and the classification frequency is 80-200Hz, so that the particle size of the finally obtained crushed material satisfies D10>0.35μm, D50=0.7-2.0μm, D90<10μm, D100<30μm.

[0161] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0162] The method for producing lithium iron phosphate from iron hydroxyphosphate according to the fifth embodiment of the present invention includes mixing iron hydroxyphosphate with a high iron phosphorus ratio and iron hydroxyphosphate with a low iron phosphorus ratio, mixing with lithium phosphate and lithium iron phosphate low-carbon product materials in a predetermined ratio, adding a carbon source and additives to form a mixed material, and then subjecting the mixed material to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain a lithium iron phosphate product. This method combines iron hydroxyphosphate with a high iron phosphorus ratio and iron hydroxyphosphate with a low iron phosphorus ratio, and introduces lithium phosphate and lithium iron phosphate low-carbon product materials, which makes it difficult for the lithium iron phosphate low-carbon product material to secondary growth during the sintering process, increases steric hindrance, reduces the aggregation of lithium iron phosphate particles, improves the circularity of lithium iron phosphate particles, and provides more and smaller particles, thereby improving the press density and electrochemical performance of the lithium iron phosphate material.

[0163] Hereinafter, the specific steps and effects of the method for preparing lithium iron phosphate using iron hydroxyphosphate of the present invention will be described in more detail with reference to some specific examples, but the protection scope of the present invention is not limited thereto. EXAMPLES

[0164] The method for producing lithium iron phosphate from iron hydroxyphosphate according to this embodiment includes the following steps S1 to S9.

[0165] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 4‰ mass fraction phosphoric acid and a 5‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0166] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0167] In step S3, an excess of 40% hydrogen peroxide solution is added to the ferrous sulfate solution, and then a phosphoric acid solution and a 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution, so that the iron-phosphorus supply ratio in the mixed slurry satisfies the iron-phosphorus molar ratios: Fe / P=1.490 and Fe / P=1.460, respectively. Ammonia water is then added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is kept at room temperature for 3 hours, and then washed with water and filtered under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0168] In step S4, the iron hydroxyphosphate precursor is flash-evaporated in a flash evaporator to dry it, and the inlet temperature of the flash evaporator is controlled to 200° C., and sintered in an air atmosphere at high temperatures of 535° C. and 560° C. for 5 h.

[0169] In step S5, the sintered material is pulverized using a mechano mill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed using a ribbon mixer at a frequency of 35 Hz for 1 h to obtain iron hydroxyphosphate products with a high iron-phosphorus ratio and a high specific surface area, and iron hydroxyphosphate products with a low iron-phosphorus ratio and a low specific surface area.

[0170] FIG. 12 shows an SEM spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 1.

[0171] FIG. 14 shows an XRD spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 1.

[0172] In step S6, iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area is mixed with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a ratio of 3:7, and then blended with lithium phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03. A carbon source mixture consisting of sucrose and polyethylene glycol and a doping amount of 2500 ppm is added to form a mixed material. The carbon content of the product is 1.3%.

[0173] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.60 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0174] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 760°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling, and the sintered material is pulverized by a jet mill, the air pressure is controlled to 0.3Mpa, and the classification frequency is controlled to 130Hz, to obtain pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm.

[0175] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0176] The SEM spectrum of the lithium iron phosphate positive electrode material produced in Example 1 is shown in FIG.

[0177] The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 1 is shown in FIG. EXAMPLES

[0178] The method for producing lithium iron phosphate from iron hydroxyphosphate according to this embodiment includes the following steps S1 to S9.

[0179] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 4‰ mass fraction phosphoric acid and a 5‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0180] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0181] In step S3, an excess of 40% hydrogen peroxide solution is added to the ferrous sulfate solution, and then phosphoric acid solution and 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution so that the iron-phosphorus supply ratio in the mixed slurry satisfies the iron-phosphorus molar ratios: Fe / P=1.490 and Fe / P=1.460, respectively. Ammonia water is then added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is heated to 60°C and kept at that temperature for 3 hours, and then washed with water multiple times and filtered under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0182] In step S4, the iron hydroxyphosphate precursor is flash-evaporated in a flash evaporator to dry it, and the inlet temperature of the flash evaporator is controlled to 200° C., and sintered in an air atmosphere at high temperatures of 535° C. and 560° C. for 5 h.

[0183] In step S5, the sintered material is pulverized in a mechanomill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed for 1 hour using a ribbon mixer at a frequency of 35 Hz to obtain iron hydroxyphosphate with a high iron-phosphorus ratio and a high specific surface area, and iron hydroxyphosphate with a low iron-phosphorus ratio and a low specific surface area.

[0184] FIG. 16 shows an SEM spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 2.

[0185] FIG. 18 shows an XRD spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 2.

[0186] In step S6, iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area is mixed with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a ratio of 3:7, and then blended with iron phosphate, lithium phosphate, and lithium carbonate in a molar ratio of Li:Fe:P=1.03:1:1.03. A carbon source mixture consisting of sucrose and polyethylene glycol and a doping amount of 2200 ppm is added to the mixture to give a carbon content of 1.35% in the product.

[0187] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.62 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0188] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 765°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling. The sintered material is pulverized by a jet mill, the air pressure is controlled to 0.3Mpa, and the classification frequency is controlled to 130Hz, to obtain pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm.

[0189] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0190] The SEM spectrum of the lithium iron phosphate positive electrode material produced in Example 2 is shown in FIG.

[0191] The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 2 is shown in FIG. EXAMPLES

[0192] The method for producing lithium iron phosphate from iron hydroxyphosphate according to this embodiment includes the following steps S1 to S9.

[0193] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 4‰ mass fraction phosphoric acid and a 5‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0194] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0195] In step S3, phosphoric acid solution and 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution so that the iron-phosphorus supply ratio in the mixed slurry satisfies the iron-phosphorus molar ratios: Fe / P=1.485 and Fe / P=1.465, respectively. Next, an excess of 40% hydrogen peroxide solution is added to the ferrous sulfate solution, and ammonia water is added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is heated to 60°C and kept at that temperature for 3 hours, and then washed with water multiple times and filtered under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0196] In step S4, the iron hydroxyphosphate precursor is flash-evaporated and dried in a flash evaporator, and the blowing and intake temperatures of the flash evaporator are controlled to 200° C., and the mixture is sintered in an air atmosphere at high temperatures of 540° C. and 560° C. for 5 hours.

[0197] In step S5, the sintered material is pulverized in a mechanomill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed for 1 hour using a ribbon mixer at a frequency of 35 Hz to obtain iron hydroxyphosphate with a high iron-phosphorus ratio and a high specific surface area, and iron hydroxyphosphate with a low iron-phosphorus ratio and a low specific surface area.

[0198] FIG. 20 shows an SEM spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 3.

[0199] FIG. 22 shows an XRD spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 3.

[0200] In step S6, iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area is mixed with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a ratio of 3:7, and then blended with iron oxide, lithium phosphate, lithium carbonate, and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03. A carbon source mixture consisting of sucrose and polyethylene glycol and a doping amount of 2500 ppm is added to form a mixed material. The carbon content of the product is 1.3%.

[0201] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.60 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0202] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 760°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling, and the sintered material is pulverized by a jet mill, the air pressure is controlled to 0.3Mpa, and the classification frequency is controlled to 130Hz, to obtain pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm.

[0203] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0204] The SEM spectrum of the lithium iron phosphate positive electrode material produced in Example 3 is shown in FIG.

[0205] The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 3 is shown in FIG. EXAMPLES

[0206] The method for producing lithium iron phosphate from iron hydroxyphosphate according to this embodiment includes the following steps S1 to S9.

[0207] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 4‰ mass fraction phosphoric acid and a 5‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0208] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0209] In step S3, an excess of 40% hydrogen peroxide solution is added to the ferrous sulfate solution, and then a phosphoric acid solution and a 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution, so that the iron-phosphorus supply ratio in the mixed slurry satisfies the iron-phosphorus molar ratios: Fe / P=1.490 and Fe / P=1.460, respectively. Ammonia water is then added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is kept at room temperature for 3 hours, and then washed with water and filtered under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0210] In step S4, the iron hydroxyphosphate precursor is flash-evaporated in a flash evaporator to dry it, and the inlet temperature of the flash evaporator is controlled to 200° C., and sintered in an air atmosphere at high temperatures of 535° C. and 555° C. for 5 h.

[0211] In step S5, the sintered material is pulverized in a mechanomill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed for 1 hour using a ribbon mixer at a frequency of 35 Hz to obtain iron hydroxyphosphate with a high iron-phosphorus ratio and a high specific surface area, and iron hydroxyphosphate with a low iron-phosphorus ratio and a low specific surface area.

[0212] FIG. 24 shows an SEM spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 4.

[0213] FIG. 26 shows an XRD spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 4.

[0214] In step S6, hydroxy iron phosphate with a high iron phosphorus ratio and a high specific surface area and hydroxy iron phosphate with a low iron phosphorus ratio and a low specific surface area are mixed in a ratio of 3:7, and then mixed with lithium phosphate and lithium iron phosphate electrode sheet material in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol with a carbon content of 1.3% in the product and titanium dioxide with a doping amount of 2800 ppm are added to form a mixed material. The lithium iron phosphate electrode sheet material is obtained by crushing and sieving the waste lithium iron phosphate positive electrode sheet to separate the foil material and the lithium iron phosphate electrode sheet raw material, and sintering the lithium iron phosphate electrode sheet raw material in an inert atmosphere, with the sintering temperature being 400°C and the sintering time being 4 hours, and then crushing until the particle size is 3 μm.

[0215] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.60 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0216] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 760°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling, and the sintered material is pulverized by a jet mill, the air pressure is controlled to 0.3Mpa, and the classification frequency is controlled to 130Hz, to obtain pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm.

[0217] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0218] The SEM spectrum of the lithium iron phosphate positive electrode material produced in Example 4 is shown in FIG.

[0219] The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 4 is shown in FIG. EXAMPLES

[0220] The method for producing lithium iron phosphate from iron hydroxyphosphate and lithium iron phosphate low-carbon product materials according to this embodiment includes the following steps S1 to S9.

[0221] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 4‰ mass fraction phosphoric acid and a 5‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0222] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0223] In step S3, an excess of 40% hydrogen peroxide solution is added to the ferrous sulfate solution, and then a phosphoric acid solution and a 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution, so that the iron-phosphorus supply ratio in the mixed slurry satisfies the iron-phosphorus molar ratios: Fe / P=1.490 and Fe / P=1.460, respectively. Ammonia water is then added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is kept at room temperature for 3 hours, and then washed with water and filtered under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

[0224] In step S4, the iron hydroxyphosphate precursor is flash-evaporated in a flash evaporator to dry it, and the inlet temperature of the flash evaporator is controlled to 200° C., and sintered in an air atmosphere at high temperatures of 535° C. and 560° C. for 5 h.

[0225] In step S5, the sintered material is pulverized in a mechanomill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed for 1 hour using a ribbon mixer at a frequency of 35 Hz to obtain iron hydroxyphosphate with a high iron-phosphorus ratio and a high specific surface area, and iron hydroxyphosphate with a low iron-phosphorus ratio and a low specific surface area.

[0226] FIG. 28 shows an SEM spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 5.

[0227] FIG. 30 shows an XRD spectrum of the iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area produced in Example 5.

[0228] In step S6, the iron hydroxyphosphate with high iron phosphorus ratio and high specific surface area is mixed with the iron hydroxyphosphate with low iron phosphorus ratio and low specific surface area in a ratio of 3:7, and then mixed with lithium phosphate and lithium iron phosphate low carbon product material in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture of sucrose and polyethylene glycol with a carbon content of 1.3% in the product and titanium dioxide with a doping amount of 2500ppm are added to form a mixed material. The important manufacturing parameters of the lithium iron phosphate low carbon product material are: the grain size of the sand milling slurry is controlled to 0.45μm, 300ppm of titanium dioxide is doped, the sintering temperature is 500℃, and the sintering time is 8 hours.

[0229] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.60 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0230] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 760°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling, and the sintered material is pulverized by a jet mill, the air pressure is controlled to 0.3Mpa, and the classification frequency is controlled to 130Hz, to obtain pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm.

[0231] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0232] The SEM spectrum of the lithium iron phosphate positive electrode material produced in Example 5 is shown in FIG.

[0233] The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 5 is shown in FIG.

[0234] The method for producing lithium iron phosphate from iron hydroxyphosphate according to this embodiment includes the following steps S1 to S9.

[0235] In step S1, ferrous sulfate, a by-product of titanium white, is added to a 6‰ mass fraction phosphoric acid and a 4‰ mass fraction sodium hydroxide solution for purification, and then purified by pressure filtration to obtain a ferrous sulfate solution.

[0236] In step S2, phosphoric acid is added to the ferrous sulfate solution in a molar ratio of n(Fe):n(phosphoric acid)=1:0.15 to lower the pH value of the ferrous sulfate solution.

[0237] In step S3, an excess of 10% hydrogen peroxide solution is added to the ferrous sulfate solution, and then phosphoric acid solution and 30% ammonium dihydrogen phosphate solution are added to the ferrous sulfate solution so that the iron-phosphorus supply ratio satisfies the iron-phosphorus molar ratio: Fe / P=1.440. Next, ammonia water is added to the ferrous sulfate solution to form a mixed slurry. The mixed slurry is kept at room temperature for 2 hours, washed with water, and filtered under pressure to form an iron hydroxyphosphate precursor.

[0238] In step S4, the iron hydroxyphosphate precursor is flash evaporated in a flash evaporator to dry it, and the inlet temperature of the flash evaporator is controlled to 200° C., and sintered in an air atmosphere at a high temperature of 520° C. for 2 h.

[0239] In step S5, the sintered material is pulverized in a mechano mill to control the particle size so that D10≧1.0 μm, D50:6-15 μm, and D90≦60 μm, and then mixed in a ribbon mixer at 35 Hz for 1 h to obtain an iron hydroxyphosphate product with a single iron-phosphorus ratio and a single specific surface area.

[0240] In step S6, ferric hydroxyphosphate and lithium phosphate are mixed in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol so that the carbon content in the product is 1.2% and titanium dioxide with a doping amount of 3000 ppm are added to form a mixed material.

[0241] In step S7, the mixed material is sand-milled, the sand-milling particle size is controlled to 0.65 μm, a nano-sized sand-milling slurry is obtained, and the nano-sized sand-milling slurry is spray-dried. The intake temperature is controlled to 220°C, the exhaust temperature is controlled to 100°C, and the blowing frequency is controlled to 80 Hz, to obtain a spray material with a spray particle size D50 = 20 to 40 μm.

[0242] In step S8, the sprayed material is put into a box furnace and sintered under a nitrogen gas atmosphere, the heating rate is 3°C / min, the sintering temperature is 765°C, and the sintering time is 10h. Then, the sintered material is obtained through natural cooling. The sintered material is pulverized by a jet mill, the air pressure is controlled to 0.35Mpa, and the classification frequency is controlled to 140Hz, and the pulverized material with particle sizes of D10>0.35μm, D50=0.8~1.8μm, D90<10μm, and D100<30μm is obtained.

[0243] In step S9, the crushed material is further sieved, and then processed into a lithium iron phosphate product, such as batch synthesis and packaging.

[0244] In order to verify the product quality of the lithium iron phosphate positive electrode material manufactured by the method for manufacturing lithium iron phosphate from iron hydroxyphosphate according to the embodiment of the present invention, the lithium iron phosphate positive electrode material manufactured in the above-mentioned Examples 1 to 5 and Comparative Example 1, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are dispersed in N-methylpyrrolidone in a mass ratio of 90:5:5, and uniformly dispersed by ball milling, and then coated on aluminum foil and vacuum dried to manufacture a positive electrode sheet. The electrolyte is 1 mol / L LiPF6, the solvent volume ratio is EC:DMC:EMC=1:1:1, the separator is Celgard polypropylene film, and the metallic lithium sheet is the negative electrode, and they are assembled together into a button-type half cell. The test voltage range is 2.0V to 3.75V, and the battery is charged to 3.75V by a constant current and constant voltage charging method, and discharged to 2.0V by a constant current discharging method, and the charge and discharge current is 0.1C for 2 cycles, and the test results are shown in Table 1. The charge / discharge curve (0.1C) of the button-type half cell assembled using the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention is shown in FIG. 32, and the charge / discharge curve (1C) of the button-type half cell assembled using the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention is shown in FIG. 33.

[0245] Table 1: Test items and test results of Examples 1 to 5 and Comparative Example 1 [Table 1]

[0246] Comparing the test results obtained by testing based on the above-mentioned Examples and Comparative Examples, the button-type half cells manufactured using the lithium iron phosphate positive electrode materials in Examples 1 to 5 had significantly improved initial charge / discharge specific capacity at 0.1C and discharge specific capacity at 1C compared to Comparative Example 1.

[0247] From the above, the method for producing lithium iron phosphate from iron hydroxyphosphate according to the embodiment of the present invention uses ferrous sulfate, which is a by-product of titanium white, to produce iron sulfate, and then adds and reacts with other materials to produce iron hydroxyphosphates with different iron-phosphorus ratios, and then undergoes different sintering processes to obtain iron hydroxyphosphate products with high iron-phosphorus ratios and high specific surface areas, and iron hydroxyphosphate products with low iron-phosphorus ratios and low specific surface areas. Iron hydroxyphosphate with high iron-phosphorus ratios and high specific surface areas and iron hydroxyphosphate with low iron-phosphorus ratios and low specific surface areas are mixed, and then mixed with a lithium source in a predetermined ratio, and then a carbon source and additives are added to form a mixed material, and the mixed material is subjected to processes such as sand milling, spray drying, sintering, sieving, batch synthesis, and packaging to obtain a lithium iron phosphate product. This method mixes and combines iron hydroxyphosphate with high iron-phosphorus ratio and iron hydroxyphosphate with low iron-phosphorus ratio, and mixes and combines the two types of iron hydroxyphosphate to form a combination of large particles and small particles, which helps to improve the press density of the lithium iron phosphate material and improve the electrochemical performance. The button-type half-cell assembled with the lithium iron phosphate positive electrode material prepared by this method has good stability and electrochemical performance, and the method requires low reaction temperature, short reaction time, low equipment requirements, simple process flow, improves production efficiency, and is suitable for large-scale industrial production.

[0248] In the description of this specification, a description referring to the terms "one embodiment", "several embodiments", "examples", "specific examples", "several examples", etc. means that the specific features, structures, materials or characteristics described in the combination of the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the exemplary expressions of the above terms are not necessarily limited to the same embodiment or example. In addition, the specific features, structures, materials or characteristics described can be appropriately combined in any one or more embodiments or examples. In addition, if not mutually inconsistent, a person skilled in the art can combine or combine different embodiments or examples described in this specification and features of different embodiments or examples.

[0249] Although embodiments of the present invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and objectives of the present invention, and that the scope of the present invention is limited by the claims and their equivalents.

Claims

1. Step S1: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, and purifying the ferrous sulfate solution by pressure filtration; Step S2: adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution; Step S3: adding hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia water to the ferrous sulfate solution, and then reacting them for a certain period of time to form a mixed slurry. The mixed slurry is kept warm for a certain period of time, and then washed with water several times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios; Step S4: flash evaporating the iron hydroxyphosphate precursor in a flash evaporator to dry it, and then sintering it at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas; Step S5: grinding the sintered material in a Mechano Mill and mixing in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; Step S6 of mixing the iron hydroxyphosphate having a high iron-phosphorus ratio and the iron hydroxyphosphate having a low iron-phosphorus ratio in a predetermined ratio, and then blending the mixture with a lithium source and an iron source in a predetermined ratio, and adding a certain amount of a carbon source and an additive to form a mixed material; Step S7: sand milling the mixed material to obtain a nano-sized sand milling slurry, and spray drying the nano-sized sand milling slurry to obtain a spray material; Step S8: putting the sprayed material into a box furnace to sinter it to obtain a sintered material, and pulverizing the sintered material with a jet mill to obtain a pulverized material; Step S9, the crushed material is further screened, batch synthesized, packaged and the like to obtain lithium iron phosphate product.

1. A method for producing lithium iron phosphate from iron hydroxyphosphate, comprising the steps of:

2. In the step S1, the mass ratio of the ferrous sulfate: the phosphorus source: the precipitant is 1:[0.001-0.005]:[0.005-0.007], the purification reaction temperature is 40° C., the reaction pH value is 2.2-2.5, the reaction time is 1 h, the phosphorus source is one or more of phosphoric acid, monoammonium phosphate, diammonium phosphate, and sodium phosphate, and the precipitant is one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, and ammonia water. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

3. In step S2, the amount of phosphoric acid added is n(Fe):n(phosphoric acid)=1:0.15 in molar ratio. In step S3, when the iron-phosphorus supply blend ratio in the mixed slurry satisfies the iron-phosphorus molar ratio: Fe / P=1.475 to 1.490, iron hydroxyphosphate having a high iron-phosphorus ratio can be formed, and when the iron-phosphorus supply blend ratio in the mixed slurry satisfies the iron-phosphorus molar ratio: Fe / P=1.460 to 1.475, iron hydroxyphosphate having a low iron-phosphorus ratio can be produced. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

4. In step S3, the number of washings may be multiple. The first washing is to wash off mainly the impurities of magnesium, manganese, and sulfur, and the last washing is to add ammonia water diluted 1:1 to adjust the pH value to 6.5 to 7.0 and remove SO 4 2- The ions are washed off, the concentration of the hydrogen peroxide solution is 30% to 60%, and the mixed slurry is kept at room temperature for 3 hours. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

5. The step S3 is Step S311 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S312: adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40° C.; then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing them uniformly to form an ammonium phosphate mixed solution; Step S313: adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then keeping the mixed slurry at room temperature for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

6. In step S4, the intake temperature of the flash evaporator is controlled to 220±20°C, the exhaust temperature is controlled to 110±5°C, the sintering atmosphere is air, the sintering temperature is set to 535-560°C, and the sintering time is set to 4-5 hours. In step S5, the particle size is controlled so that D10≧1.0 μm, D50: 6-15 μm, and D90≦60 μm, the mixing frequency of the mixer is controlled to 35±2 Hz, and the mixing time is set to 1-2 hours. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

7. In step S5, the iron hydroxyphosphate having a high iron-phosphorus ratio has a high specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.460 to 1.480, and the specific surface area is BET=15 to 20 m. 2 The iron hydroxyphosphate having a low iron-phosphorus ratio has a low specific surface area, and the iron-phosphorus molar ratio satisfies Fe / P=1.440 to 1.460, and the specific surface area is BET=5 to 10 m. 2 / g is satisfied, A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

8. In the step S6, the molar ratio of Li:Fe:P is [1.03-1.04]:1:[1.03-1.04], the amount of the carbon source added is based on the carbon content in the final product being between 1.2% and 1.6%, the lithium source is one or more of lithium phosphate, lithium carbonate, lithium iron phosphate electrode sheet material, and lithium iron phosphate low carbon product material, the iron source is one or more of iron phosphate and iron oxide, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, the additive is one or more selected from titanium dioxide, ammonium metavanadate, and diniobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm, and the step In step S7, the sand milling particle size in the sand milling slurry is controlled to be between 0.45 and 0.75 μm; in the spray drying, the intake temperature is 200 to 220 ° C, the exhaust temperature is 80 to 110 ° C, the blowing frequency is 80 Hz, and the spray particle size in the spray material is controlled to be between D50 = 20 to 40 μm; in step S8, the sintering atmosphere is nitrogen gas, the sintering temperature is 750 to 780 ° C, the heating rate is 3 ° C / min, the sintering time is 8 to 12 h, and then the sintered material can be obtained through natural cooling; in the grinding process, the air pressure is controlled to be between 0.2 to 0.4 MPa, the classification frequency is 80 to 200 Hz, and the particle size of the ground material is made to satisfy D10 > 0.35 μm, D50 = 0.7 to 2.0 μm, D90 < 10 μm, and D100 < 30 μm; A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

9. Step S1: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, and purifying the ferrous sulfate solution by pressure filtration; Step S2: adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution; Step S3: adding hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution, and ammonia water to the ferrous sulfate solution in this order, and then reacting them for a certain period of time to form a mixed slurry. The mixed slurry is heated and kept at the temperature for a certain period of time, and then washed with water several times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios; Step S4: flash evaporating the iron hydroxyphosphate precursor in a flash evaporator to dry it, and then sintering it at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas; Step S5: grinding the sintered material in a Mechano Mill and mixing in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; Step S6 of mixing iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a predetermined ratio, and then blending the mixture with iron phosphate, lithium phosphate, and lithium carbonate in a predetermined ratio and adding a certain amount of a carbon source and an additive to form a mixed material; Step S7: sand milling the mixed material to obtain a nano-sized sand milling slurry, and spray drying the nano-sized sand milling slurry to obtain a spray material; Step S8: putting the sprayed material into a box furnace to sinter it to obtain a sintered material, and pulverizing the sintered material with a jet mill to obtain a pulverized material; Step S9, the crushed material is further screened, batch synthesized, packaged and the like to obtain lithium iron phosphate product. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

10. The step S3 is Step S321 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S322: adding phosphoric acid solution to the oxidized ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature at 30 to 40° C., and adding the resulting solution to the oxidized ferrous sulfate solution; Step S323: adding ammonia water to the ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then heating and keeping the mixed slurry for a certain period of time, and then washing the mixed slurry with water multiple times and filtering the mixed slurry under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 9.

11. Step S1: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, and purifying the ferrous sulfate solution by pressure filtration; Step S2: adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution; Step S3: adding phosphoric acid, ammonium dihydrogen phosphate solution, hydrogen peroxide solution, and ammonia water to the ferrous sulfate solution in this order, and then reacting them for a certain period of time to form a mixed slurry. The mixed slurry is heated and kept at the temperature for a certain period of time, and then washed with water several times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios; Step S4: flash evaporating the iron hydroxyphosphate precursor in a flash evaporator to dry it, and then sintering it at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas; Step S5: grinding the sintered material in a Mechano Mill and mixing in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; Step S6 of mixing iron hydroxyphosphate having a high iron-phosphorus ratio and a high specific surface area with iron hydroxyphosphate having a low iron-phosphorus ratio and a low specific surface area in a predetermined ratio, and then blending the mixture with iron oxide, lithium phosphate, lithium carbonate, and ammonium dihydrogen phosphate in a predetermined ratio and adding a certain amount of a carbon source and an additive to form a mixed material; Step S7: sand milling the mixed material to obtain a nano-sized sand milling slurry, and spray drying the nano-sized sand milling slurry to obtain a spray material; Step S8: putting the sprayed material into a box furnace to sinter it to obtain a sintered material, and pulverizing the sintered material with a jet mill to obtain a pulverized material; Step S9, the crushed material is further screened, batch synthesized, packaged and the like to obtain lithium iron phosphate product. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

12. The step S3 is Step S331: adding a phosphoric acid solution to the ferrous sulfate solution, then adding water to ammonium dihydrogen phosphate powder to dissolve it, preparing an ammonium dihydrogen phosphate solution with a concentration of 30%, setting the dissolution temperature at 30 to 40° C., and adding the resulting solution to the ferrous sulfate solution; Step S332 of adding excess hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S333: adding ammonia water to the ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then heating and keeping the mixed slurry for a certain period of time, and then washing the mixed slurry with water multiple times and filtering the mixed slurry under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 11.

13. Step S1: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, and purifying the ferrous sulfate solution by pressure filtration; Step S2: adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution; Step S3: adding hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia water to the ferrous sulfate solution, and then reacting them for a certain period of time to form a mixed slurry. The mixed slurry is then kept at room temperature for a certain period of time, and then washed with water several times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios; Step S4: flash evaporating the iron hydroxyphosphate precursor in a flash evaporator to dry it, and then sintering it at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas; Step S5: grinding the sintered material in a Mechano Mill and mixing in a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; Step S6: mixing the iron hydroxyphosphate having a high iron phosphorus ratio and the iron hydroxyphosphate having a low iron phosphorus ratio in a predetermined ratio, and then blending the mixture with the lithium phosphate and lithium iron phosphate electrode sheet material in a predetermined ratio, and adding a certain amount of carbon source and additives to form a mixed material; Step S7: sand milling the mixed material to obtain a nano-sized sand milling slurry, and spray drying the nano-sized sand milling slurry to obtain a spray material; Step S8: putting the sprayed material into a box furnace to sinter it to obtain a sintered material, and pulverizing the sintered material with a jet mill to obtain a pulverized material; Step S9, the crushed material is further screened, batch synthesized, packaged and the like to obtain lithium iron phosphate product. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

14. The step S3 is Step S341: adding an excess of hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S342: adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40° C.; then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing them uniformly to form an ammonium phosphate mixed solution; Step S343: adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then keeping the mixed slurry at room temperature for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 13.

15. In the step S6, the manufacturing method of the lithium iron phosphate electrode sheet material includes the steps of crushing and sieving the waste lithium iron phosphate positive electrode sheet to separate the foil material and the lithium iron phosphate electrode sheet material raw material; sintering the lithium iron phosphate electrode sheet material raw material in an inert atmosphere, the sintering temperature is 400-500°C, the sintering time is 1-4 hours, and then crushing it until the particle size is 1-5 μm to obtain the lithium iron phosphate electrode sheet material; A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 13.

16. Step S1: adding ferrous sulfate, a by-product of titanium white, to a phosphorus source and a precipitant, and purifying the ferrous sulfate solution by pressure filtration; Step S2: adding an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution; Step S3: adding hydrogen peroxide solution, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia water to the ferrous sulfate solution, and then reacting them for a certain period of time to form a mixed slurry. The mixed slurry is then kept at room temperature for a certain period of time, and then washed with water several times and filtered under pressure to form iron hydroxyphosphate precursors having different iron-phosphorus ratios; Step S4: flash evaporating the iron hydroxyphosphate precursor in a flash evaporator to dry it, and then sintering it at high temperature for a certain period of time to obtain iron hydroxyphosphate precursor products with different iron-phosphorus ratios and different specific surface areas; Step S5: grinding the sintered material with a mechano mill and mixing with a ribbon mixer to obtain iron hydroxyphosphate products with different iron-phosphorus ratios and different specific surface areas; Step S6: mixing the iron hydroxyphosphate with a high iron phosphorus ratio and the iron hydroxyphosphate with a low iron phosphorus ratio in a predetermined ratio, and then blending with lithium phosphate and lithium iron phosphate low carbon product materials in a predetermined ratio, and adding a certain amount of carbon source and additives to form a mixed material; Step S7: sand milling the mixed material to obtain a nano-sized sand milling slurry, and spray drying the nano-sized sand milling slurry to obtain a spray material; Step S8: putting the sprayed material into a box furnace to sinter it to obtain a sintered material, and pulverizing the sintered material with a jet mill to obtain a pulverized material; Step S9, the crushed material is further screened, batch synthesized, packaged and the like to obtain lithium iron phosphate product. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 1.

17. The step S3 is Step S351 of adding an excess of hydrogen peroxide to the ferrous sulfate solution and continuing oxidation for a certain period of time; Step S352: adding water to ammonium dihydrogen phosphate powder to dissolve it to prepare an ammonium dihydrogen phosphate solution with a concentration of 30%, and dissolving it at a temperature of 30 to 40° C.; then adding phosphoric acid solution and ammonia water to the ammonium dihydrogen phosphate solution and stirring and mixing them uniformly to form an ammonium phosphate mixed solution; Step S353: adding the ammonium phosphate mixed solution to the oxidized ferrous sulfate solution, adjusting the pH value of the solution to 3.00±0.02, reacting for a certain period of time to form a mixed slurry, and then keeping the mixed slurry at room temperature for a certain period of time, and then washing with water multiple times and filtering under pressure to form iron hydroxyphosphate precursors with different iron-phosphorus ratios.

17. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 16.

18. The step S6 is Step S61: mixing iron oxide with a phosphorus source, a lithium source, a primary carbon source, and a dopant, and then adding water and stirring to obtain a slurry; Step S62: wet grinding the slurry, spray drying, sintering under a nitrogen gas atmosphere, and airflow pulverization are performed in this order to obtain a pulverized lithium iron phosphate low-carbon product material; S63, mixing the iron hydroxyphosphate with a high iron phosphorus ratio and the iron hydroxyphosphate with a low iron phosphorus ratio in a predetermined ratio, and then blending with lithium phosphate and lithium iron phosphate low carbon product materials in a predetermined ratio, and adding a certain amount of secondary carbon source and additives to form a mixed material; 17. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 16.

19. In step S61, the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate, the lithium source is lithium carbonate and / or lithium hydroxide, the primary carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, a molar ratio of iron in the iron oxide to phosphorus in the phosphorus source is n(Fe):n(P)=(0.96-1):1, a molar ratio of lithium in the lithium source to iron in the iron oxide is n(Li):n(Fe)=(1.02-1.05):1, the dopant is a metal oxide, and the metal is at least one of Ti, V, Nb, and Mg. At least one kind of carbon source is added; in step S63, the carbon content in the lithium iron phosphate low carbon product material is between 0.2% and 0.5%, and the molar ratio in the mixed material is Li:Fe:P=[1.03-1.04]:1:[1.03-1.04]; the secondary carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the primary carbon source and the secondary carbon source added is based on the carbon content in the final product being between 1.2% and 1.6%; the additive is one or more selected from titanium dioxide, ammonium metavanadate, and diniobium pentoxide, and the doping amount is controlled to be between 300 and 3000 ppm; 20. A method for producing lithium iron phosphate from iron hydroxyphosphate according to claim 18.

20. Applying the method for producing lithium iron phosphate from iron hydroxyphosphate according to any one of claims 1 to 19, A lithium-ion battery positive electrode material.

21. 21. A lithium ion battery cathode material comprising the lithium ion battery cathode material of claim 20. A lithium-ion battery characterized by:

Citation Information

Patent Citations

  • Hairyusanno seiseiho

    JP1976009097A

  • Method for producing lithium ion secondary battery anode active material

    JP2013127898A